TOURISM CULTURE AND INTERNATIONAL ECONOMIC RELATIONS - Muhsina Juraboyeva (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the interrelation between tourism culture and international economic relations. It highlights how tourism contributes to cross-cultural understanding, promotes national heritage, and influences global trade and investment flows. The study also emphasizes the economic benefits of tourism, including job creation, foreign exchange earnings, and regional development. Furthermore, the paper explores how tourism culture shapes international collaboration, impacts diplomatic relations, and serves as a tool for soft power in global economics.